Temas socioambientais: contribuições para o ensino de ciências naturais - FERREIRA, Darlene Teixeira (Universidade Federal do Pará, 2012)
The introduction of social and environmental themes in classroom nowadays, especially in natural science secundary education classes, may mean the arising of a efficient strategy to form critic and acting citizens in society. These themes, along with contents of physics, chemestry and biology promote a more complex comprehension of our planet’s state and create the possibility of discussions related to sustainability.To contribute for the qualification of science teaching, we made this research, which aim is an investigation on natural science teachers’ knowledge about current social and environmental questions and its relations to teaching and learning process, mainly in education for sustainability field, that has multiple dimensions.The research is framed in the qualitative mode. We adopted, as a methodological strategy, a single case study (YIN, 2005) and, as unit case, the Federal University of Pará Aplication School. The researche’s subjects were secondary education school teachers. We adopted the projective interview and assystematic observation as instruments to collect data. To interpret the information we used the discursive textual analysis (MORAES E GALIAZZI, 2007). The research results also pointed to elementary discussions of social and environmental issues in classroom. However, some teachers have already introduced superficial discussions on sustainability during their daily work . The main theoretical references were: Leff (2002), Veiga (2005), Sachs (2007), Delizoicov, Angotti e Pernambuco (2009), Figueiredo (2004), Gadotti (2008).